Extracellular Recording Systems: A Glial‐Silicon Nanowire Electrode Junction Enabling Differentiation and Noninvasive Recording of Slow Oscillations from Primary Astrocytes (Adv. Biosys. 4/2020). Issue 4 (14th April 2020) - Saracino, Emanuela; Maiolo, Luca; Polese, Davide; Semprini, M.; Borrachero‐Conejo, Ana Isabel; Gasparetto, Jacopo; Murtagh, Stefano; Sola, Margherita; Tomasi, Lorenzo; Valle, Francesco; Pazzini, Luca; Formaggio, Francesco; et al.
Abstract : In article number 1900264, Annalisa Convertino, Valentina Benfenati, and co‐workers show that a forest of randomly oriented gold coated‐silicon nanowires (Au/SiNWs) induces the differentiation of astrocytes showing complex structural and functional properties in vivo. Tight junctions between the Au/SiNWs‐device and astrocytes processes enables extracellular recording of slow‐frequency oscillations generated only by differentiated cells.